Analisis Peran Pelatihan Pembinaan UMKM Berbasis Teknologi Informasi Untuk Meningkatkan SDM Pada Pegawai UMKM Mie Gacoan Karawang - Putrikasari, Oktaviani; S, Sungkono (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Micro, small and medium enterprises (MSMEs) in Indonesia are one of the business sectors that can help the government provide employment opportunities for the community. In order to keep Indonesia's economy moving forward, the government has allocated a lot of funds to encourage the millennial generation to become entrepreneurs, especially in technology-based businesses such as startups. This is a training event aimed at MSME players. The target is to increase the ability of MSME players to develop their businesses with the help of information technology. They will be taught about financial management and e-commerce, and will become more proficient in using IT. The people who took part came from sub-districts in Karawang Regency. This MSME course involves fifty people. Mie Gacoan Karawang MSME employees gain an understanding of e-commerce and the importance of technology to develop MSME products so they can increase income. One way to carry out these activities is to use various promotional platforms available such as YouTube, Instagram and Google Business. MSME participants can learn the basics of using this platform..